Wedelolactone facilitates Ser/Thr phosphorylation of NLRP3 dependent on PKA signalling to block inflammasome activation and pyroptosis. (12th July 2020) - Pan, Hao; Lin, Yuqing; Dou, Jianping; Fu, Zhen; Yao, Yanqing; Ye, Shanyu; Zhang, Saixia; Wang, Neng; Liu, Aijun; Li, Xican; Zhang, Fengxue; Chen, Dongfeng
Abstract: Objectives: Wedelolactone exhibits regulatory effects on some inflammatory diseases. However, the anti‐inflammatory mechanism of wedelolactone has not been entirely unravelled. Therefore, the present study focuses on investigating the mechanism of wedelolactone on NLRP3 inflammasome in macrophages and its influence on MSU‐induced inflammation. Materials and Methods: BMDM, J774A.1 and PMA‐differentiated THP‐1 macrophages were primed with LPS and then stimulated with ATP or nigericin or MSU crystal in the presence or absence of wedelolactone. The cell lysates and supernatants were collected to detect NLRP3 inflammasome components such as NLRP3, ASC and caspase 1, as well as pyroptosis and IL‐1β production. In addition, the anti‐inflammatory effects of wedelolactone on MSU‐induced peritonitis and arthritis mice were also evaluated. Results: We found that wedelolactone broadly inhibited NLRP3 inflammasome activation and pyroptosis and IL‐1β secretion. Wedelolactone also block ASC oligomerization and speck formation. The inhibitory effects of wedelolactone were abrogated by PKA inhibitor H89, which also attenuated wedelolactone‐enhanced Ser/Thr phosphorylation of NLRP3 at PKA‐specific sites. Importantly, wedelolactone could abate MSU‐induced IL‐1β production and neutrophils migration into peritoneal cavity, and reduced caspase 1 (p20) and IL‐1β expression in the joint tissue of MSU‐induced arthritis. Conclusion: Our results indicate that wedelolactone promotes the Ser/Thr phosphorylation of NLRP3 to inhibit inflammasome activation and pyroptosis partly through potentiating PKA signalling, thus identifying its potential use for treating MSU‐induced peritonitis and gouty arthritis. Abstract : Wedelolactone is a major active ingredient of the traditional medicinal herb eclipta, which demonstrates a broad‐spectrum inhibition effect on NLRP3 inflammasome activation triggered by multiple stimuli. Wedelolactone suppresses NLRP3 inflammasome assembly, pyroptosis and IL‐1β secretion through heightening PKA‐dependent NLRP3 phosphorylation. Importantly, wedelolactone could alleviate NLRP3‐related inflammation in MSU‐induced peritonitis and gouty arthritis.